2003
DOI: 10.1002/path.1344
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of immature plasmacytoid dendritic cells (plasmacytoid monocytes) and myeloid dendritic cells in primary cutaneous melanomas

Abstract: The present study has analysed the distribution and phenotype of dendritic cells (DCs) in primary cutaneous melanomas and sentinel lymph nodes by immunohistochemistry. In primary melanomas, an increase of DCs was found in the epidermis and the peritumoural area. Intraepidermal DCs were mostly CD1a(+)/Langerin(+) Langerhans cells. Peritumoural DCs included a large population of DC-SIGN(+)/mannose-receptor(+)/CD1a(-) DCs, a small subset of CD1a(+) DCs, and, remarkably, plasmacytoid monocytes/plasmacytoid DCs (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
208
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 260 publications
(226 citation statements)
references
References 57 publications
15
208
0
3
Order By: Relevance
“…Extracellular HMGB1 mediates endotoxin lethality and inflammation [32,[42][43][44][45][46]. These findings suggest that HMGB1 may be involved in regulating the function of PDC, which have been implicated in the pathogenesis of cancer [47,48] and chronic inflammatory conditions like systemic lupus erythematosus and allergy [49][50][51].…”
Section: Introductionmentioning
confidence: 92%
“…Extracellular HMGB1 mediates endotoxin lethality and inflammation [32,[42][43][44][45][46]. These findings suggest that HMGB1 may be involved in regulating the function of PDC, which have been implicated in the pathogenesis of cancer [47,48] and chronic inflammatory conditions like systemic lupus erythematosus and allergy [49][50][51].…”
Section: Introductionmentioning
confidence: 92%
“…Two other studies on dendritic cell infiltrate in primary cutaneous melanoma have reported that the dendritic cell infiltrate was rare and mostly confined to the peritumoral areas. 15,21 We therefore evaluated the dendritic cell infiltrate as Absent, if 0 cells were to be found and Present otherwise. However, the DC-LAMP infiltration of the peritumoral area was more frequent and it was graded as Absent/Few versus Dense.…”
Section: Evaluation Of Immunostainingmentioning
confidence: 99%
“…11 However, the DC maturation capacity is altered in tumor-bearing hosts and DC subsets in tumors are predominantly immature/nonactivated cells that mediate tolerance to the tumor by inducing Tcell anergy and regulatory T cells. 5,[12][13][14][15] The failure of immune cells in the tumor microenvironment to mount an effective immune response and their promotion of tumor progression instead may be rooted in a constitutive activation of signal transducer and activator of transcription 3 (STAT3) in both tumor cells and immune cells. STAT3 is a point of convergence for numerous oncogenic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…lupus erythematosus disease, psoriasis and rheumatoid arthritis) [1,51,52], allergic diseases (i.e. contact dermatitis and nasal mucosa polyps) [53] and in tumors [2,54] (Table 1). However, the mechanisms underlying this effect are elusive.…”
Section: Reviewmentioning
confidence: 99%
“…The relevance of PDCs in cancer immunosurveillance has been recently shown in mice [68,69], where TLR9-activated PDCs lead to the regression of subcutaneous B16 melanoma tumors, by orchestrating the sequential activation of NK cells, MDCs and CD8 + T cells. The characterization of PDCs has been performed in a variety of human neoplasms [54,[70][71][72]. However, the potential impact of PDCs for cancer immunity is based largely on in vitro studies of circulating PDCs, while PDCs detectable at the tumour site (tumor-associated PDCs, TAPDCs) are poorly characterized.…”
Section: Reviewmentioning
confidence: 99%